Efektivitas Penggunaan Media Pembelajaran melalui Media Sosial pada Mata Kuliah Pangkas Rambut Dasar - Evi Veronika Sipayung; Ifa Nurhayati; Ade Novi Nurul Ihsani; Anik Maghfiroh (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
The development of information technology and social media has driven changes in the learning process in higher education, including the use of more flexible and easily accessible learning media for students. Social media allows the presentation of learning materials in various formats, such as video and non-video media, which can support the learning process, particularly in practical courses such as basic hairdressing. This study aims to determine the effectiveness of using social media as a learning medium in basic hairdressing courses. The study used a quantitative approach with a pretest-posttest design. The research instrument was an objective test whose validity and reliability were tested, with an item correlation value of 0.514 and a Cronbach's Alpha value of 0.947 for the pretest and 0.933 for the posttest. Data analysis was performed by calculating the average value and gain score. The results showed that video media achieved a gain score of 50, while non-video media achieved a gain score of 72.67. Thus, the use of social media as a learning medium is effective in improving student learning outcomes, with non-video media demonstrating higher effectiveness.